Serhij Sannikov, Znaky prysutnosti. Večerja Hospodnja v konteksti baptystsʹkoi͏̈ sakramentolohii͏̈ = Sergii Sannikov, Signs of Presence. The Lord’s Supper Within the Baptist Sacramentology - Šeludʹko, Mychajlo (Bogoslovs'ki rozdymi, 2024)
The monograph by Serhiy Sannikov, "Signs of Presence: The Lord’s Supper in the Context of Baptist Sacramentology", explores the theology of the Eucharist within the Baptist tradition, examining its spiritual and theological dimensions. This work is part of a trilogy addressing core Baptist practices, with prior volumes covering baptism and future volumes focusing on ordination. The author connects his research to broader global theological trends, addressing the evolving spiritual needs in postmodern and emerging contexts.